Analysis of Critical Thinking Capabilities in Solving the Problems of Building Space Based on the Student’s Introvert Personality Type - Nila Arnawati; Sukmawati Sukmawati; Baharullah Baharullah (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to describe students' critical thinking skills based on introverted personality types in solving spatial problems in solving fifth grade classroom building problems at SD Hartaco Indah Makassar. This research uses descriptive qualitative. Data were collected through tests, questionnaires, interviews, observations, and documentation. This study uses data analysis techniques, which consist of stages of data collection, data reduction, data presentation, and drawing conclusions. Research results Students' critical thinking skills in solving spatial problems are encouraged and sharpened their minds in solving problems by training their minds in solving problems and linking mathematics learning problems with everyday life in a concrete and contextual way. The personality type of introverted students is a personality that is more comfortable with oneself, quiet who is called a closed person, prefers thoughts, concepts, ideas, analysis, prefers to work alone rather than working in groups, tends to be more careful in solving problems and solving problems. mathematics independently. The conclusion of this study is that the students' critical thinking skills in solving spatial problems can be seen from the introverted students' personality types